Repair of Enophthalmus in Neglected Tetrapod Zygoma Fracture with Diced Cartilage Graft and Fascia Lata Sling Graft: A Case Report - Bangun, Kristaninta; Halim, Jessica; Handayani, Siti (Lingkar Studi Bedah Plastik Foundation, 2022)
Introduction: Zygoma fractures with orbital involvement, are the most common midfacial traumas, which cause severe aesthetic and functional sequelae. Late reduction of orbital floor fracture may result in entrapment of orbital soft tissue, predisposing the occurrence of enophthalmos. This article aimed to report enopthalmus correction in neglected tetrapod zygoma fracture case with autologous diced cartilage graft and fascia lata graft.Case Presentation: A 42-year-old female was injured in a traffic accident 8 years ago. Facial fracture was not repaired surgically, resulting in facial asymmetry and diplopia. Physical examination revealed right-sided zygoma deformity, 5mm dystopia, depressed malar eminence, gaze restriction and enophthalmus on the right eye. 3D CT scan confirmed a malunited neglected tetrapod zygoma fracture.Result: Corrective osteotomy was performed to reconstruct the tetrapod zygoma fracture using combination of bicoronal, infracilliary, and maxillary vestibular approach. 4-point fixation and stepladder modification was used. 1.6 cc of cartilage-derived diced bone graft was inserted on the posterior orbital floor to repair enophthalmos. Six months follow-up revealed improved dystopia and malar prominence. Additional surgery was done to repair scleral show and smoothen and augment lower lid volume using 4.5x0.6 cm fascia lata graft hammocked from the medial canthus to lateral orbital bone.Discussion & Conclusion: Long neglected zygoma fracture possessed a difficulty in reconstructing malunited zygoma articulation. Good aesthetic and functional outcome are achievable following use of diced cartilage and fascia lata graft for enophthalmus correction in neglected zygoma-orbital fracture, suggesting the role of fascia lata sling graft for treatment of scleral show and lower lid volume replacement.